Design of nanostructured polymeric materials for radiation shielding of ionizing radiations - Noor Azman, Nurul Zahirah Binti (Curtin University, 2013)
This study seeks to provide a novel approach for producing technologically viable new radiation shielding materials to meet the safety requirements for use in medical X-ray imaging facilities. The approach was based on dispersing micro-sized and nano-sized heavy element fillers into polymeric materials using different filler dispersion methods such as melt-mixing, ion implantation and electrospinning. These materials have high potential application for shielding of X-rays in diagnostic radiology purposes.